Narrative-focused Group Counseling Improves Intervention Outcomes in Women With Obesity - Ajami, Marjan; Kagawa, Masaharu; Roshanmehr, Farnaz; McKian, Somayeh Sadat; Radfar, Mohammad; Vazirijavid, Roya; Houshiarrad, Anahita; Esmaeili, Mina; Taghizadeh-Hesary, Farzad; Lovell, Lyndah; Abdollahi, Morteza (Journal of nutrition education and behavior, 2022)
OBJECTIVE: To investigate the effects of narrative group counseling combined with diet modification and exercise plans on weight loss in Iranian women with obesity. DESIGN: Parallel 2-arm clinical trial. PARTICIPANTS: Fifty-six Iranian women with obesity (aged 18-50 years). INTERVENTION: The intervention group included weekly diet, exercise, and narrative-focused group counseling, whereas the comparison group included dietary modification and exercise sessions for 8 months (32 sessions). MAIN OUTCOME MEASURE: Anthropometric and body composition parameters, blood biochemical parameters (high-density lipoproteins, low-density lipoproteins, triglycerides, fasting blood sugar, ghrelin, obestatin), physical activities, and appetite scores. ANALYSIS: McNemar test was used for the variables that were not normally distributed and for scaling. Furthermore, t tests were used to compare quantitative variables with normal distributions. The original P (0.05) was adjusted to P = 0.0031 using the Bonferroni correction. RESULTS: Weight, body mass index, body fat proportion, and hip circumference decreased significantly in the intervention vs comparison group. Serum low-density lipoproteins, triglycerides, total cholesterol, fasting blood sugar, appetite score, and ghrelin decreased, whereas obestatin increased significantly in the intervention vs comparison group. CONCLUSIONS AND IMPLICATIONS: Narrative-focused group counseling combined with traditional strategies was effective in achieving significant changes in weight, body mass index, and appetite. Future studies with a more diverse audience and a longer follow-up are warranted.
Keywords: weight loss, narrative-focused group counseling; Cholesterol; lidé; krevní glukóza; Lipoproteins, LDL; Obesity; cholesterol; Lipoproteins, HDL; Counseling; Female; Body Mass Index; poradenství; Iran; lipoproteiny HDL; Humans; index tělesné hmotnosti; obezita; Triglycerides; Írán; Ghrelin; Blood Glucose; lipoproteiny LDL; ženské pohlaví; ghrelin; triglyceridy; obestatin; metabolic biomarkers